IMPROVING DMOS’ LOCAL COORDINATION EFFORTS THROUGH WEB 2.0 - Pattanaro, Giulio; Maurizio, Marek; van der Borg, Jan (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2013)
This paper investigates the role Web 2.0 technologies and applications may play in improving Destination Management Organisations’ ability to coordinate tourism stakeholders at local level. More specifically, the paper illustrates the structure and functioning of an online platform giving Destination Management Organisations the possibility to integrate and display the tourism promotional and informative contents which have been developed by a wide range of local players. The benefits as well as the potential implementation issues of this platform are illustrated and discussed and further research on the topic is finally suggested.